Second language proficiency modulates conflict-monitoring in an oculomotor Stroop task: evidence from Hindi-English bilinguals - Singh, Niharika; Mishra, Ramesh K. (Frontiers in Psychology, 2013)
Many studies have confirmed the presence of a bilingual advantage which is manifested as enhanced cognitive and attention control. However, very few studies have investigated the role of second language proficiency on the modulation of conflict-monitoring in bilinguals. We investigated this by comparing high and low proficient Hindi-English bilinguals on a modified saccadic arrow Stroop task under different monitoring conditions, and tested the predictions of the bilingual executive control advantage proposal. The task of the participants was to make an eye movement towards the colour patch in the same colour as the central arrow, ignoring the patch to which the arrow was pointing. High-proficient bilinguals had overall faster saccade latency on all types of trials as compared to the low proficient bilinguals. The overall saccadic latency for high proficiency bilinguals was similarly affected by the different types of monitoring conditions, whereas conflict resolution advantage was found only for high monitoring demanding condition. The results support a conflict-monitoring account in a novel oculomotor task and also suggest that language proficiency could modulate executive control in bilinguals.